Analysis of the Effect of Using the SIPLah Application on User Satisfaction in Procuring Elementary School Books in Pangkalpinang City - Hamidah, Hamidah; Rizan, Okkita (ISB Atma Luhur, 2024)
The advancement of information technology has become more widespread across various sectors, particularly in education. The integration of information technology has increasingly simplified many aspects of human life. This study aims to evaluate the impact of the SIPLah (School Procurement Information System) application on user satisfaction in the procurement of books for elementary schools. SIPLah is a government-provided digital platform designed to streamline the procurement of goods and services within schools, promoting greater transparency, efficiency, and accountability. The research data was collected through surveys involving SIPLah users, such as school principals, teachers, and administrative staff engaged in book procurement. The study measured variables including ease of use, system reliability, procurement process speed, and user satisfaction with the procurement outcomes. The analysis revealed that the SIPLah application has a significant impact on user satisfaction. Among the factors studied, ease of use and system reliability had the most positive influence. However, some respondents reported technical challenges, such as delays in data updates and insufficient technical support. To enhance future user satisfaction, the study recommends improvements in technical services and system optimization.